Isotherm and Kinetic Studies of Flouride Removal on Activated Carbon obtained from Coconut Shell - Shehu, Zaccheus; Lamayi, Wilson Danbature; Kwarson, Pipdok Solomon; Yirankinyuk, Fai Frederick (Innoriginal: International Journal of Sciences, 2019)
Activated carbon was prepared using coconut shell according to standard method. Langmuir and Freundlich isotherms as well as pseudo-first order and pseudo-second order were studied. The Freundlich isotherm confirmed suitable match with the experimental information with high correlation coefficient. The kinetic parameters confirmed that the maximum favourable order for the adsorption technique is the pseudo-second order kinetic. Outcomes showed that activated carbon prepared from coconut shell was very powerful in the defluoridation of water with approximately 73.1 % fluoride removal at a reaction time of fifty minutes, temperature of 30oC, and adsorbent dose of 1.5 g.